Imaging and clinical outcomes of COVID-19- vs. non-COVID-19-related cerebral venous thrombosis - Maxhuni, Toska; Doeppner, Thorsten R.; Braun, Tobias; Emde, Julia; Struffert, Tobias; Dembek, Thomas; Huttner, Hagen B.; Juenemann, Martin B.; Gerner, Stefan T. (Frontiers in Stroke, 2024)
Background: Cerebral venous thrombosis (CVT) is a rare but serious subtype of stroke.Several studies reported an increased incidence of CVT after either infection or vaccination, however, data on clinical characteristics, radiological profile and outcomes of these patients with CVT as only severe symptom of Cov19 infection or vaccination compared to patients with non-Cov19-related CVT are still scarce.: We performed a retrospective monocentric study over 10-year period(January 2013 until December 2022) including consecutive patients with confirmed diagnosis of CVT based on imaging of the cerebral venous system. Patients were categorized into CoV19-CVT (either due to infection or post-vaccination) versus non-CoV19-CVT and compared regarding demographics, risk factors, clinical characteristics, imaging findings as well as outcome (at discharge, at 6 months and last follow-up). Further, subanalyses were performed for the comparison between CoV19-infection related CVT versus vaccination-related CVT patients. Results: Overall, 122 patients with suspected CVT were identified. After exclusion of patients with missing data(n=20) or missing imaging of the cerebral venous system(n=31), 71 patients with confirmed CVT remained for final analyses. Of those, 11 patients had CoV19-CVT (infection n=3, vaccination n=8) and 60 patients had non-CoV19-CVT. There were no differences regarding median age (Cov19 40 [IQR: 22-70] vs. non-CoV19 41 [IQR:27-64] or percentage of female sex among both groups. A lower rate of CVT-risk factors was observed in the Cov19-group, but without significant differences. No patient with CoV19-CVTpresented with impaired consciousness on presentation, only 30 % had focal neurological deficits compared to 51.7% in the control group. The rate of CVT-related intracranial hemorrhage or venous infarcts were 27.3% / 9.1 % in the Cov19-groups versus 30% /16.7% in non-Cov19 patients. The mortality rate at discharge was 9.1% in CoV19-CVT versus 3.3% in non-Cov19-CVT without differences in functional outcomes during the follow-up period.Subanalyses comparing Cov19-infection related CVT versus Cov19-vaccination related CVT revealed no significant differences in clinical, imaging or treatment characteristics.In this monocentric study, there was no signal for a higher severity of CoV19-CVT compared to non-CoV19-CVT regarding clinical characteristics, imaging profile or outcomes in patients with CVT only. Larger observational data with sophisticated workup of CVT-patients are needed to confirm our results.